Underground storage for decarbonisation: Trade-offs between hydrogen, natural gas, and carbon dioxide - Aliaksei Patonia; Martin Lambert; Ning Lin; Mark Shuster (The Oxford Institute for Energy Studies, 2025)
As decarbonisation efforts accelerate globally, the role of large-scale underground storage for energy and climate-related gases - natural gas, hydrogen, and carbon dioxide - is becoming increasingly important. While the demand for natural gas as a transition fuel is expected to rise at least until the end of the decade, clean hydrogen is increasingly gaining prominence in long-term decarbonisation plans. At the same time, growing volumes of CO2 need to be permanently sequestered to reduce its concentration in the atmosphere. Since all the three gases can technically be stored in the same four types of geological formations - salt and rock caverns, deep aquifers, and depleted hydrocarbon fields - their simultaneous underground management raises important technical, economic, and strategic questions that are yet to be comprehensively addressed. This paper therefore examines the suitability, opportunities, and challenges associated with large-scale geological storage of natural gas, hydrogen, and carbon dioxide, focusing on the four key subsurface structures. It finds that not all formations are equally suitable for all gases: salt and rock caverns and smaller depleted fields are optimal for hydrogen and natural gas storage, while large-scale aquifers and depleted reservoirs are better suited for permanent sequestration of carbon dioxide. Therefore, in the short- to mid-term, CO₂ storage is unlikely to interfere with hydrogen and natural gas operations, given differing physicochemical properties and storage site preferences. It is also noteworthy that while hydrogen and natural gas are expected to be put into storage to be extracted later, for CO₂ by contrast the intention is that it will be sequestered permanently. The analysis also highlights that while hydrogen and natural gas could technically compete for the same storage structures, hydrogen's significantly higher storage costs and the absence of a liquid market currently limit its competitiveness. Therefore, large-scale hydrogen storage will require targeted government support and strategic policy frameworks. Crucially, the value proposition of hydrogen storage lies in its ability to enhance energy system flexibility, energy security, and long-term decarbonisation, which may justify a premium over natural gas in selected applications. The study concludes by advocating for integrated underground storage planning that moves beyond narrow techno-economic considerations to account for social, political, and systemic factors - ensuring that hydrogen, natural gas, and CO₂ storage are developed in a coherent, complementary, and sustainable manner.
Keywords: 330; decarbonization; energy; Hydrogen; net-zero-carbon